Ta’śīru Mahārah al-Qirā’ah ‘alā Qudrati Tarjamah al-Qur’ān bi al-Ma’had - Rini, Fitri Setyo; Wardani, Aisah Liana (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This research aims to find out the reading ability of student class two KMI, the ability to translate the Qur’an for student class two KMI, and the effect of reading skills on the ability to translate the Qur’an on tarjamatu al-Qur’an material for class two KMI Darussalam Gontor Islamic Boarding School. This type of research is a quantitative survey. Samples were taken from 25% of the population using the proportionate stratified random sampling method, totaling 148 students. The data was taken using a test that had been tested for validity and reliability. The data analysis technique used is descriptive analysis, requirements testing, and hypothesis testing using nonparametric rank Spearman. The result showed that the reading ability of class two KMI is quite good, with an average (Mean) of 62,38. The ability to translate the Qur’an in the Tarjamatu al-Qur’an for class two KMI is quite good, with an average (Mean) of 72,53. From the influence analysis using Spearman’s rank correlation analysis, it can be concluded that reading ability affects the ability to translate the Qur’an. This is evidenced by the smaller significance value of 0.000 of the probability value 0.05.